Coverage and determinants of birth dosage of newborn immunization in rural areas of Dehradun District, Uttarakhand, India: A community-based cross-sectional study - Prakash Kumar; Abhishek Kumar; Bhavana Saini; Mahendra Singh; Vartika Saxena (Wolters Kluwer Medknow Publications, 2023)
Backgrounds: The Universal Immunization Program of India is one of the most cost-effective interventions in public health. Missing or delaying vaccination may elicit an uncertain immune response in the body, making the population susceptible to vaccine-preventable diseases. The objectives of this study were to determine the coverage of newborn immunization for birth doses under the National Immunization Schedule and its epidemiological determinants in the rural areas of the Dehradun district, Uttarakhand. Materials and Methods: A community-based cross-sectional study was conducted for a period of one year with a sample size of 570. World Health Organization (WHO) 30 Cluster sampling technique was used with 19 children in each cluster. The data on determinants were collected using a semi-structured, pre-designed schedule through a house-to-house survey. Multivariate analysis was conducted to identify factors associated with immunization coverage, taking the significance level as P < 0.05. Results: The coverage of the Bacillus Calmette-Guérin vaccine, oral polio vaccine zero dose and hepatitis B birth dose were 100%, 91.9%, and 58.8%, respectively in the study area with an overall prevalence of incomplete coverage of newborn immunization as 42.5%. The most cited reason for children being unimmunized with birth doses was the unavailability of vaccines at the birthplace center (29.6%). Conclusions: The prevalence of incomplete coverage of newborn immunization was quite high, which was undermining the holistic approach of the National Immunization Program. Vaccine availability and accessibility at the birthplace with capacity building and training of the healthcare workers may be considered to ensure coverage of birth doses.